Self‐Assembly of Bowl‐Shaped Naphthalimide‐Annulated Corannulene. Issue 1 (5th November 2019) - Renner, Rebecca; Stolte, Matthias; Würthner, Frank
Abstract: The self‐assembly of a bowl‐shaped naphthalimide‐annulated corannulene of high solubility has been studied in a variety of solvents by NMR and UV/Vis spectroscopy. Evaluation by the anti‐cooperative K 2 ‐ K model revealed the formation of supramolecular dimers of outstanding thermodynamic stability. Further structural proof for the almost exclusive formation of dimers over extended aggregates is demonstrated by atomic force microscopy (AFM) and diffusion ordered spectroscopy (DOSY) measurements as well as by theoretical calculations. Thus, herein we present the first report of a supramolecular dimer of an annulated corannulene derivative in solution and discuss its extraordinarily high thermodynamic stability with association constants up to >10 6  M −1 in methylcyclohexane, which is comparable to the association constants given for planar phthalocyanine and perylene bisimide dyes. Abstract : All about that bowl : Supramolecular dimers formed upon self‐assembly of a naphthalimide‐annulated corannulene derivative have been investigated and characterized. They show distinct H‐type exciton coupling and intense fluorescence as well as an extraordinarily high thermodynamic stability in solution.